1998
DOI: 10.1016/s0167-2789(97)00280-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic localized modes: Discrete breathers. Existence and linear stability

Abstract: We present some examples of detailed analysis of intrinsic localized modes in lattices, using the accurate numerical methods derived from the proof of existence of MacKay-Aubry. We report on some improvements on the methods, which are then used to the fullest to obtain the Floquet analysis of the breather solutions. Such calculations are possible taking into account the whole lattice, without any approximations. This yields an unprecedented detail of the mechanisms that govern instabilities in discrete breathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 19 publications
2
51
0
1
Order By: Relevance
“…for describing energy and charge transport and storage in biological macromolecules [5]. Recently, discrete breathers have been experimentally observed in coupled optical waveguides [6], in charge-density wave systems [7], in magnetic systems [8], and in arrays of coupled Josephson junctions [9].Although a discrete breather under quite general conditions is linearly stable [1,3,10] (and thus no perturbations grow exponentially), there are many questions remaining concerning the long-time fate of perturbed breathers. In a previous paper [11], some of these questions were addressed considering a particular model, the discrete nonlinear Schrödinger (DNLS) equation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…for describing energy and charge transport and storage in biological macromolecules [5]. Recently, discrete breathers have been experimentally observed in coupled optical waveguides [6], in charge-density wave systems [7], in magnetic systems [8], and in arrays of coupled Josephson junctions [9].Although a discrete breather under quite general conditions is linearly stable [1,3,10] (and thus no perturbations grow exponentially), there are many questions remaining concerning the long-time fate of perturbed breathers. In a previous paper [11], some of these questions were addressed considering a particular model, the discrete nonlinear Schrödinger (DNLS) equation.…”
mentioning
confidence: 99%
“…Although a discrete breather under quite general conditions is linearly stable [1,3,10] (and thus no perturbations grow exponentially), there are many questions remaining concerning the long-time fate of perturbed breathers. In a previous paper [11], some of these questions were addressed considering a particular model, the discrete nonlinear Schrödinger (DNLS) equation.…”
mentioning
confidence: 99%
“…These regions appear to happen near bifurcations which connect the site-centered and bond-centered stationary breathers (see Ref. [12]), and the subject is being investigated in greater detail [6]. It is difficult to estimate how wide these regions are, other than by means of numerical simulation.…”
Section: Longitudinal Moving Breathers In 2d Latticesmentioning
confidence: 99%
“…Just like in 1D models, it was observed that a too strong on-site potential hinders mobility, and favours the pinning of the excitations into stationary breathers (intrinsic localized modes). A too weak on-site potential usually destroys the breather by broadening and radiation into the background, due to resonances with the phonon band [12]. In between these extremes, there exists an ample region where it is easy to obtain moving breathers, with a more or less wide range of energies and velocities.…”
Section: Longitudinal Moving Breathers In 2d Latticesmentioning
confidence: 99%
“…In the linear stability problem, oscillatory instabilities arise through Hamiltonian Hopf bifurcations yielding eigenvalues with nonzero real as well as imaginary parts. Well-known examples for one-dimensional lattices are, e.g., two-site localized "twisted" modes [2,3], discrete dark solitons ("dark breathers") [4,5], spatially periodic or quasiperiodic nonlinear standing waves [6], and gap modes in diatomic chains [7,8]. In the latter contexts, oscillatory instabilities may play an important role in the initial stages of breather formation and thermalization processes [6,8].…”
Section: Introductionmentioning
confidence: 99%